Consumer Reactions to Product Failure: An Attributional Approach - Folkes, Valerie S. (Journal of Consumer Research, 1984)
Journal Article Consumer Reactions to Product Failure: An Attributional Approach Get access Valerie S. Folkes Valerie S. Folkes Search for other works by this author on: Oxford Academic PubMed Google Scholar Journal of Consumer Research, Volume 10, Issue 4, March 1984, Pages 398–409, https://doi.org/10.1086/208978 Published: 01 March 1984 Article history Received: 01 April 1983 Revision received: 01 July 1983 Published: 01 March 1984